VD_FINDINFO ML / 2014 / 135 vom 3. Juni 2014 - VD Tribunal cantonal (2014)
DROIT D'ÊTRE ENTENDU, FICTION DE LA NOTIFICATION, NOTIFICATION IRRÉGULIÈRE, NULLITÉ | 29 al. 2 Cst., 84 al. 2 LP, 107 al. 2 CPC (CH), 138 CPC (CH), 253 CPC (CH), 53 CPC (CH)